Explaining a Paradox of Democracy: The Role of Institutions in Female Enfranchisement - Anna Maria Koukal; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2017)
Switzerland is known for its highly developed direct democracy. However, Swiss women were enfranchised at the federal level only in 1971 and in many cantons even later. We analyze the role of direct democracy in the delayed Swiss enfranchising process by investigating a novel dataset covering referenda among males about enfranchising women. Applying a difference-in-differences approach, we shed light on the conditions under which strong local direct democracy becomes a barrier to women's suffrage. Our results are consistent with direct democracy having two effects: it boosts men's demand to enfranchise women, but it also increases the price for men to do so. Depending on the specific conditions of the vote, the former or the latter effect dominates.
Keywords: D72; J16; N24; N44; P16; 330; women's suffrage; municipal institutions; direct democracy